Aristotle on logic and nature - Lindén, Jan-Ivar, 1959- (Aristote, traductions et études., 2019)
The impact of Aristotle cannot be overestimated, covering not only the "first philosophy", which later was to become "metaphysics", but several different areas, ranging from ethics and politics to rhetoric and poetry. A special status belongs to the fundamentals of thinking, treated in the logical writings. Another core of Aristotelian philosophy concerns the philosophy of nature? issues of life and soul, natural kinds, animal movement, nature in all its aspects, including the translunar sphere of heavenly bodies. The psychology of De anima is part of this philosophy of nature, but at the same time includes a noetic sphere, indicating another dimension of human life, which enables true knowledge and truly virtuous actions. These aspects of Aristotelian philosophy are often studied separately. While there are several important works on Aristotelian logic, ethics and psychology, the aim of the current volume is to offer perspectives on the interrelatedness of these domains.0.